The GPUVerify Method: a Tutorial Overview - Donaldson, Alastair (Electronic Communications of the EASST, 2014)
I present a tutorial overview demonstrating the key technique used by GPUVerify, a static verification tool for graphics processing unit (GPU) kernels.  The technique is a method for translating a massively parallel GPU kernel into a sequential program such that correctness of the sequential program implies data race-freedom of the parallel kernel.